Design, modelling and characterization of comb drive MEMS gap-changeable differential capacitive accelerometer. (February 2021) - Li, Ru; Mohammed, Zakriya; Rasras, Mahmoud; Elfadel, Ibrahim (Abe) M.; Choi, Daniel
Highlights: MEMS accelerometer with high capacitance sensitivity and compact footprint. Study of an analytical modal of anti-gap spacing on sensitivity. Optimization of finger gap spacing and anti-finger gap spacing ratio. Numerical simulation and experimental validation of device performance. Abstract: This paper presents design optimization, numerical modelling, fabrication and characterization of a single-axis comb drive MEMS gap-changeable differential capacitive accelerometer with a compact footprint of 2 mm × 2 mm. High sensitivity is achieved by optimizing the ratio of the anti-finger gap to finger gap spacing. It is found that a gap ratio of 3.44 leads to a displacement sensitivity of 0.0139 µm/g and a capacitive sensitivity of 80 fF/g. Finite element analysis is used to find the mode shape and frequency. Scanning electron microscope and capacitance-voltage measurements are employed to confirm the devices work. An enlarged static capacitance of 14.46 ± 0.42 pF is measured due to the enlarged stator anchor width. Electrical sensitivity of 35.93 mV/g is obtained by using the capacitance readout circuit at the system level, and the electrical sensitivity is practically constant over the frequency range of 100–200 Hz.